"I don't like wonky carrots"- an exploration of children's perceptions of suboptimal fruits and vegetables. (May 2020) - Makhal, Annesha; Thyne, Maree; Robertson, Kirsten; Mirosa, Miranda
Abstract: Children's perceptions of suboptimal fruits and vegetables have not been studied in the suboptimal foods domain. Using two qualitative research methods, this study investigates children's (N = 97) edibility perceptions of suboptimal produce with varied appearance defects. The results show that unlike adult samples previously studied, children are more accepting of suboptimal produce. Defects in shape, size, and certain colour defects were positively perceived, reflecting retailers' opportunities to market suboptimal produce. High levels of brown discolorations and superficial blemishes were not acceptable, implying that produce with such defects could be repurposed as ingredients in foods prepared and sold in-store. These implications reflect retailers' opportunities in marketing suboptimal produce to children, who by their familial influence may also be able to get families to buy and consume suboptimal produce. The importance of familiarity in improving suboptimal food acceptance is also recognised for future research to explore.